2016
DOI: 10.18632/oncotarget.10284
|View full text |Cite
|
Sign up to set email alerts
|

Dynein axonemal heavy chain 8 promotes androgen receptor activity and associates with prostate cancer progression

Abstract: To gain insight into cellular factors regulating AR action that could promote castration resistant prostate cancer (CRPC), we performed a genome-wide RNAi screen for factors that promote ligand-independent AR transcriptional activity and integrated clinical databases for candidate genes that are positively associated with prostate cancer metastasis and recurrence. From this analysis, we identified Dynein Axonemal Heavy Chain 8 (DNAH8) as an AR regulator that displayed higher mRNA expression in metastatic than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…According to the description in the STRING or GeneCards database, DNAH8 is a force-generating protein of the respiratory cilia and is also involved in sperm motility. In addition, DNAH8 is highly expressed in prostate cancer [21]. Titin appears to be a key component of the vertebrate striated muscles [22].…”
Section: Functional Enrichment Of the Unique Hbmec-ev Proteinsmentioning
confidence: 99%
“…According to the description in the STRING or GeneCards database, DNAH8 is a force-generating protein of the respiratory cilia and is also involved in sperm motility. In addition, DNAH8 is highly expressed in prostate cancer [21]. Titin appears to be a key component of the vertebrate striated muscles [22].…”
Section: Functional Enrichment Of the Unique Hbmec-ev Proteinsmentioning
confidence: 99%
“…Another speculation, to hypothesize a novel therapeutic strategy in positive ERG prostate cancer patients, was based on the analysis of the co-expressed protein-coding genes and lncRNAs. The upregulation of the Wnt pathway and its inhibition emerged as a promising strategy against prostate cancer [ 46 ], although thinking about the most appropriate approach is imperative for the pervasive role of the Wnt pathway in normal tissue homeostasis. Several approaches have been taken into account for inhibiting the Wnt pathway, such as LGK974, a drug that targets the Wnt-specific acyltransferase porcupine, and the tankyrase inhibitor XAV939 [ 46 ], and the growing interest in the inhibition of the Wnt pathway in prostate cancer models confirms the validity of the therapeutic hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…An integrated analysis of RNA-Seq data and qRT-PCR results revealed that DNAH5 may play an important role in the development of colorectal cancer, and it might be useful for diagnosis, prognosis prediction and therapy [33]. DNAH8 has been reported to be a novel regulator of the androgen receptor that is associated with metastatic tumors and poor prognosis in patients with prostate cancer [34]. In invasive micropapillary carcinomas of the breast, DNAH9 has a substantially elevated mutation rate [35].…”
Section: Discussionmentioning
confidence: 99%